2012
DOI: 10.1177/1470593112451388
|View full text |Cite
|
Sign up to set email alerts
|

Design orientation

Abstract: The notion of design thinking or 'design as a state-of-mind' and its articulation through design orientation implies that true innovation is a company-wide phenomenon and cannot be left to single individuals as a marginalized function within a company. Many innovative companies try to integrate technical performance with an aesthetic vision -which is not to be confused with styleas the driving force of the organization. Based on our findings and analysis, we put forward theoretical propositions that cover vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The study extends the existing knowledge of effects among researched concepts when measuring the role of design orientation. Our results are consistent with most research findings reported in previous studies (i.e., Borja de Mozota, 2003b;British Design Council, 2006Koostra, 2009;Moll et al, 2007;Venkatesh et al, 2012). Design orientation appears to indirectly impact the company performance and market success through customer orientation and by influencing the managerial approach.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The study extends the existing knowledge of effects among researched concepts when measuring the role of design orientation. Our results are consistent with most research findings reported in previous studies (i.e., Borja de Mozota, 2003b;British Design Council, 2006Koostra, 2009;Moll et al, 2007;Venkatesh et al, 2012). Design orientation appears to indirectly impact the company performance and market success through customer orientation and by influencing the managerial approach.…”
Section: Resultssupporting
confidence: 92%
“…According to Venkatesh et al (2012), design orientation (DO) involves a strategic way of employing a company-wide vision that integrates design into the creation of customer value. It has also been identified as a factor integrating decisions at different levels of an organization and involving customers as a key element (Bloch, Brunel, & Arnold, 2003;Moll et al, 2007).…”
Section: Theoretical Background On Design and Market Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…The openness, practicality and transferability of design thinking is precisely it's strength and it may be that, as some argue, a design (thinking) attitude or mind-set across a company or organization, for example Proctor & Gamble, Mayo Health Clinic, is a recipe for innovation success (Beverland & Farrelly, 2010;Venkatesh, Digerfeldt-Mansson, Brunel, & Chen, 2012).…”
Section: Defining Design Thinkingmentioning
confidence: 99%
“…Similarly, scholars have discussed design orientation to signpost strategic approaches that rely on different types of design to deploy competitive advantage, including product design, packaging design, and graphic and interior design (Cantò et al, 2021;Moll et al, 2007;Venkatesh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%